Baseline Determination at Government Discretion Multi-Project Baselines for the First Track of Joint Implementation? - Simon Schmitz; Axel Michaelowa (Hamburg Institute of International Economics (HWWA), 2003)
The ,,first track“ of Joint Implementation under the Kyoto Protocol gives host and investor countries total freedom in choosing a baseline for a project reducing or sequestering greenhouse gases. This is due to the fact that an overly generous granting of emission credits leads to a corresponding reduction of the host country`s emission budget. Standardised, multi-project baselines can reduce transaction costs, especially in relatively homogeneous sectors such as electricity production or landfill methane collection. Host countries need capacity to calculate such baselines which currently does not exist. ,,Boundary organisations“ can bridge the gap between technical analysis and strategic considerations. Interviews with government officials and other stakeholders in East European EU accession countries lead us to the conclusion that countries have not yet realised the chances and pitfalls of baseline definition under the first track, especially as they assume that the EU will define the ,,acquis communautaire“ as the baseline. However, this would make international emissions trading more attractive than JI.
Keywords: Q25; O13; 330; Joint Implementation; baselines; institutions; host countries; Klimaschutz; Umweltabkommen; Internationale Umweltpolitik; Luftreinhaltung; Umweltauflage; Umweltorganisation; Welt